2015
DOI: 10.3109/08880018.2015.1022915
|View full text |Cite
|
Sign up to set email alerts
|

High Response Rate to Pegylated Interferon Alpha and Ribavirin Combination Therapy in Hemophilic Children with Chronic Hepatitis C; A Case-Control Study

Abstract: Scarce data is available on the efficacy of Pegylated Interferon (Peg-IFN) and Ribavirin (RBV) combination therapy in hemophilic children with chronic hepatitis C. The aim of this study was to evaluate the efficacy of Peg-IFN and RBV combination therapy for hemophilic children infected with hepatitis C virus (HCV) in comparison with adult hemophilic patients with chronic hepatitis C. A case-control study comprised 31 pediatric hemophilic patients ages under 16 years with previously untreated HCV genotype-1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Based on these findings, experts and guidelines recommended to intensify the treatment by adding RBV or prolongation of treatment to a 24-week course when patient harbor cirrhosis and/or previous history of treatment and/or NS5A RASs (20). The on-treatment response was the most important predictor of response of SVR in the IFN-based regimens; however, with the introduction of highly efficient IFN-free DAA regimens, the importance of on-treatment response faded (21)(22)(23)). In the current study, the only case with viremia at the week 4 of treatment achieved SVR; however, large-scale studies are needed to clarify the importance of on-treatment response in clinical decision-making in the IFN-free regimens era.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, experts and guidelines recommended to intensify the treatment by adding RBV or prolongation of treatment to a 24-week course when patient harbor cirrhosis and/or previous history of treatment and/or NS5A RASs (20). The on-treatment response was the most important predictor of response of SVR in the IFN-based regimens; however, with the introduction of highly efficient IFN-free DAA regimens, the importance of on-treatment response faded (21)(22)(23)). In the current study, the only case with viremia at the week 4 of treatment achieved SVR; however, large-scale studies are needed to clarify the importance of on-treatment response in clinical decision-making in the IFN-free regimens era.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, Age <24, HCV genotype‐non‐1, BMI <25 and baseline HCV RNA<600 000 IU/mL were independent predictors of SVR . A recent study on hemophilic children and adults demonstrated 83.9% and 62.9% SVR rates, respectively . Alavi‐moghaddam et al reported an excellent success rate of 95.6% in 45 non‐cirrhotic hemophiliac patients (mean age 30.4±12.6 years), of which 55.6% were infected with HCV genotype‐1 and 42.2% with HCV genotype‐3.…”
Section: Discussionmentioning
confidence: 86%
“…(8)(9)(10)(11). Moreover, on-treatment response and viral kinetic are stronger predictors of SVR to PegIFN and RBV treatment compared to baseline parameters (12,13). Among on-treatment responses, rapid virologic response (RVR) and early virologic response (EVR) were used as predictors of SVR and for response-guided therapy (4,5).…”
Section: Introductionmentioning
confidence: 99%